2001
DOI: 10.1677/joe.0.1700347
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal regulation of tight junction closure in the mouse mammary epithelium during the transition from pregnancy to lactation

Abstract: Closure of the tight junctions of the mammary epithelium has been shown to accompany the onset of copious milk secretion or lactogenesis, stage 2, in both goats and humans. Here we use injection of [ 14 C]sucrose and FITC-albumin (fluorescein isothiocyanate-albumin) into the mammary duct to follow the course of tight junction closure during lactogenesis in mice. To examine the hormonal changes responsible, we ovariectomized day 16 or 17 pregnant mice and found that closure followed ovariectomy with a mean dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
127
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(139 citation statements)
references
References 28 publications
6
127
0
1
Order By: Relevance
“…Indeed, the decrease in plasma IgG occurred when plasma P4 concentrations were still high. Moreover, P4 was shown to prevent closure of tight junctions between lactocytes in the mouse [10,11] and, when associated with E2, to enable paracellular transfer of immunoglobulins from plasma to the alveolar lumen of mammary glands in the cow [41]. In sows, Jackson et al [42] confirmed the positive role of P4 on IgG transfer by showing higher colostrum concentrations of IgG in sows treated with P4 and farrowing at 116 days of gestation instead of 114 days.…”
Section: Plasma Hormones Lactose and Igg Variations Around Parturitionmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, the decrease in plasma IgG occurred when plasma P4 concentrations were still high. Moreover, P4 was shown to prevent closure of tight junctions between lactocytes in the mouse [10,11] and, when associated with E2, to enable paracellular transfer of immunoglobulins from plasma to the alveolar lumen of mammary glands in the cow [41]. In sows, Jackson et al [42] confirmed the positive role of P4 on IgG transfer by showing higher colostrum concentrations of IgG in sows treated with P4 and farrowing at 116 days of gestation instead of 114 days.…”
Section: Plasma Hormones Lactose and Igg Variations Around Parturitionmentioning
confidence: 94%
“…It can be depicted from variations of concentrations of Ig and lactose in colostrum and plasma. This closure occurs between 24 and 36 h after the onset of parturition and is under the control of P4, cortisol and PRL [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Insulin-like growth factor 1 (IGF1; 7.6 kDa), another member of the insulin family of hormones, is found in porcine colostrum at high concentrations (Simmen et al 1990a, which decline within the first 24-36 h of lactation during the transition from colostrum to mature milk (Klobasa et al 1987, Nguyen et al 2001. In the porcine neonate, a window for transmission of macromolecules, including MbFs, is open before gut closure, which is estimated to occur within 48 h of birth (Leece 1973).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the mammary epithelium reorganizes during distinct stages of the ovarian cycle in preparation for lactation. [16][17][18] Conversely, pathogens may destabilize homotypic interactions between adjacent cells and thereby destabilize the epithelial monolayer to gain entry. 19,20 Although many of the components involved in cellular communication are known, identifying the regulatory networks that control the collective cellular response within tissues remains a challenge.…”
Section: Tissues As Dynamic Systemsmentioning
confidence: 99%